STOMACH POISON RESPONSE TO KIPAHIT LEAF EXTRACT Tithonia diversifolia AGAINST FALL ARMYWORM LARVAES Spodoptera frugiperda J. E. Smith. - Dian Dhika; Lisdayani; Nurhayati; Nor Azma Yusuf (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2021)
Corn (Zea mays L.) is an important food crop in Indonesia, whose production is threatened by the invasive pest Spodoptera frugiperda (Fall Armyworm/FAW). This pest causes significant damage to crops and drastically reduces yields. Excessive use of chemical insecticides to control FAW has caused various negative impacts. Therefore, the development of plant-based botanical insecticides is a safer and more sustainable control alternative.The purpose of this study was to observe the toxicity response of stomach poison extract of T. diversifolia kipahit leaves to S. frugiperda larvae. This study was conducted in the laboratory of the Faculty of Agriculture, Islamic University of North Sumatra, Jl. Karya Wisata Gedung Johor. Medan Johor District, Medan City, North Sumatra. With an altitude of ± 25 m above sea level (meters above sea level) with flat topography. This study was conducted in the laboratory using a Non-factorial Completely Randomized Design using several treatments, namely K0: Control, K1: 0.1%, K2: 0.2%, K3: 0.3%, K4: 0.4%, and K5: 0.5%. The stomach poison of T. diversifolia kipahit leaf extract had a very significant effect on the mortality of S. frugiperda larvae, showing that the highest mortality was at the K5 concentration (0.5%) reaching 23-90% at 2-8 HSA and the lowest percentage of larval mortality, namely the K0 concentration (control), had a mortality of 3-8% at 6-8 HSA.